Characteristics of recycled plaster of Paris at several different temperatures between 150℃ - 190℃ during recycling process / Ainun Fathiah Hamdan, Oskar Hasdinor Hassan and Nor Nazida Awang - Hamdan, Ainun Fathiah; Hassan, Oskar Hasdinor; Awang, Nor Nazida (Faculty of Art and Design, 2024)
A significant amount of solid waste is dumped by the ceramics sector, which is a worry for the environment. As well known, Kuala Kangsar, Perak, Malaysia is the location to a large ceramics industry. In Malaysia, there are landfills, but not all of them can manage solid waste perfectly. As a result, many waste disposal contractors look down on solid waste management such as for Plaster of Paris (POP). This is even more complicated when there are a handful of them who take the easy way out by disposing of POP waste by planting or dumping it into rivers and seas. This causes various problems to the environment and health. The aim of this study is to identify how to recycle waste mould into new plaster without affecting their casting performance. This paper shows the study of the effect of characteristics Recycle Plaster of Paris (RPOP) compared to New Plaster of Paris (NPOP). Drying temperatures are performed at (150℃,160℃,170℃,180℃ and 190℃) for RPOP and use the same 60% of material and 40% of water ratio and tests for porosity, absorption, setting times and particle size are performed. The results indicate that all samples of Recycled Plaster of Paris performed well and can function similarly to New Plaster of Paris at different temperatures.